The significance of political conviction - Jokubaitis, Alvydas (Politologija, 1999)
The perception of the significance ascribed to political conviction fluctuates between two extremes, namely exaggerated individualism preached by J.S. Mill and the processual thinking advocated by G. Hegel. The followers of the first author are convinced that an individual should be treated as the final source of social norms, whereas those supporting Hegel (and accordingly F. Nietzsche) tend to think that the genuine source generating social meanings is a certain power superior to an individual. It could be a system, a discourse, a structure, or some process. Such a severe juxtaposition held by followers of J.S. Mill, on the one hand, and those of Hegel, on the other hand, can only be overcome by one single way, and that is by recognizing the significance of tradition. Tradition is the intermediate link which makes it easier to account for both the individuals’ ability to express their convictions and for the existence of political institutions. A mutual relationship does exist between political structures and individual citizens. Political structures precondition the actions undertaken by human beings; however, these structures themselves are subject to changes due to human understanding. The convictions and beliefs held by individuals enable them to maintain the existence of certain political institutions. At the same time, the aforementioned institutions are the structures empowering certain individual activities. Since the Greek times, political philosophers have been seeking for something more than merely the convictions held by common citizens, that is, they were searching for principles which could not be rebuffed, metaphysical fundamentals, or eternal standards of human rationality. There was a quest for unshakable philosophical fundamentals, which seemed to be far more important than the ability of common people to comprehend each other and maintain certain traditions of political life. One could manipulate the convictions held by human beings even in the most liberal society. Nevertheless, such manipulation is far more limited in those societies the members of which actively participate in the affairs of political governing. That is, individual political convictions acquire their true meaning merely in those political cultures which are based on the active participation of their citizens in the management of political affairs. Manipulations of convictions can be resisted only in those societies, the citizens of which have not only heard of certain words shaping political discourse but also by means of their daily activities contribute to the maintenance of a certain political order which is perceived by them as the continuation of their convictions.